Impact of Long-term Grazing on Soil Organic Carbon Pools and Enzyme Activities in Semi-arid Tropical Inceptisol - Prashant Deo Singh; Sultan Singh, Avijit Ghosh*, S.K. Mahanta (Journal of the Indian Society of Soil Science, 2022)
Long-term grazing by small ruminants diminishes grass and plant covers, shifts in plant species composition, and possibly alters soil enzyme activity. To apprehend the link among grazing and soil organic carbon (SOC) and nutrient cycling enzyme, a study was conducted at 3 different stocking rates (SR1 = 1 Adult Cattle Unit (ACU) ha-1, SR2 = 2ACU ha-1, and SR3= 3 ACU ha-1) in 5 ha of pasture lands and were compared with a control pasture land. Soil samples were collected from surface and sub-surface layers to understand the variations in those parameters. In general, pasture productivity under SR1 was significantly higher than SR2 and SR3. They significantly depleted SOC (by 20%) than SR1 and control. Generally, grazing diminished particulate organic matter associated C, however, SR1 significantly increased mineral associated C. High grazing pressure significantly reduced dehydrogenase, sulphatase, and urease activities over control; however, SR1 boosted activities of phenoloxidase (33%) and peroxidase (32%) over control. Despite that SR1 recorded 25 per cent lower carbon loss than control, SR2 and SR3 had similar carbon loss to control having lower SOC in the upper soil layer. A reduced stocking rate would sustain SOC and maintain productivity and hence could be recommended in the semi-arid tropical regions.